The dairy cow as a source of wealth in America - Maxwell, Henry Greenleaf (My University, 1906)
Introduction: In every state and territory of the Union, in every county, and, almost, at least, in every village and hamlet there are cows being kept for their milk-giving qualities. In villages and towns remote from cities where "the rich are poor and the poor live in abundance" the knowledge that a dairy cow is an economical investment is well known to all incumbent with the duties of domestic affairs; in homes where the standard of living is that of the average and typical American family, the cow is kept for its economy. The writer often suspected that many keeping dairy cows were not really reducing their household expenses; because of the way in which the cow was kept, the item of expenditure for the cow's keeping would run higher than the returns from the milk the cow gave, whether it was used in the home or sold to neighbors. This suspicion is well verified by the timely statistics of the dairy cow in the “Cow Census" which is being so accurately and thoroughly collected under the supervision of the Hoards Dairyman. However, this fact does not discredit the popular idea of the people that a cow can materially reduce the expense of the household; for it is a long and common experience of the people; moreover, it is borne out by intelligently conducted experiment, and, also, is verified in the "Cow Census”. It is this popular idea that has led to this attempt at studying to what extent does the dairy cow figure in producing the wealth of this country? How far does the cow figure in the satisfying the wants of the American homes, and how many happy families owe their prosperity to the cow? To what degree is the Nation's progress and prosperity resting upon this animal?
Citation: Maxwell, Henry Greenleaf. The dairy cow as a source of wealth in America. Senior thesis, Kansas State Agricultural College, 1906.
Morse Department of Special Collections
Keywords: Agricultural Economics; Cow Census; Dairy; Theses